(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Human-Centered Design (HCD) is a user-centric approach that prioritizes understanding and meeting end-users needs throughout the design and evaluation process. This comprehensive framework outlines critical stages to ensure the development of effective, efficient, and satisfying products, services, or systems. Beginning with thorough research and discovery, the framework progresses through problem definition, ideation, prototyping, implementation, and evaluation, emphasizing iterative design and continuous improvement. Launch and post-launch strategies, documentation, and ethical considerations are integral components. This framework guides designers and teams, fostering adaptability, inclusivity, and a commitment to user satisfaction, privacy, and security. Embracing this holistic approach facilitates the creation of solutions that address current user needs and evolve in tandem with changing requirements and technological advancements.